Amazon forest dieback: assessing vulnerabilities and threats - Nobrega, Caroline Correa (2016)
In recent years, it is increasing evidences about Amazon vunerability due to land use and climate changes. Because of a positive feedback system, in which impacts intensify other impacts, some models project to the end of the century a replacement of the Amazon forest by savanna formations or semi-arid (forest dieback). Several evidence has indicated a high vulnerability of the Amazon to global climate change and local environmental impacts triggered by human activities (eg conversion to agricultural areas, construction of roads and burns). However, they are still deeply unknown the general mechanisms and standards about how these impacts affect the forest. In this thesis, I developed works that aim contribute to discussions of the subject. In each chapter, I will consider a threat that is contributing to the degradation of the Amazon. Each of the three threats discussed in the following chapters are often cited as important drivers of forest dieback. In the first chapter I evaluated the impact of forest fires at different levels of diversity of trees in a forest area next to the Amazon-Cerrado transition. Our results suggest that communities of trees in burned areas are losing more phylogenetic and functional diversity per unit of species than in unburned areas. My results indicate the existence of selection of species based on phylogenetic and functional characteristics, representing a major force of change and impoverishment (functional and phylogenetically) of these communities. In the second chapter, using high resolution images (LiDAR and hyperspectral), I evaluated the impact of a intense drought in forest areas near Madre de Dios, Peru. Thus, my results support the idea that changes in regional climate may change the structure and function of the forest. In the third chapter, I evaluated how the construction of roads in the Brazilian Amazon has contributed to deforestation in an important group of protected areas of the Amazon: the Indigenous Lands. Based on the analysis of observed impacts, I propose the establishment of buffer zones (buffers) around these reserves to reduce the negative impacts of road construction planned to be built.